Penerapan Model Project Based Learning untuk Meningkatkan Motivasi Belajar Matematika - Sagita, Dian; Khair, Baiq Niswatul; Yati, Mega Suci (Lembaga Yasin AlSys, 2023)
This research aims to determine the increase in mathematics learning motivation of class VA students at SDN 7 Cakranegara using the project based learning model. This research includes collaborative PTK research with a descriptive quantitative approach. This research was carried out in stages in two cycles. The subjects of this research are all VA class students at SDN 7 Cakranegara for the 2022/2023 academic year. The data collection methods used were observation and questionnaires. Data from motivation to learn mathematics in the form of pretest and posttest, then calculations were carried out on the results of the questionnaire. The learning motivation data was then analyzed to see improvements in the pre-cycle, cycle I and cycle II. Increased learning motivation from the results of the pretest or pre-cycle with 17 children in the low category, 5 children each in the moderate and high categories. Then it increased until cycle II, namely that there were no students with low learning motivation. Minimum students have motivation to learn in the sufficient category of 6 children, 12 children in the high category, and 9 children in the very high category. This shows that the application of the project based learning model can increase the mathematics learning motivation of class VA students at SDN 7 Cakranegara.